Implantation and development of nursing process at University Hospital - Silva, Sandra Honorato da; Takito, Clarinda; Barbiere, Doroty Leite (Revista da Escola de Enfermagem da USP, 1990)
The work relates the implantation and development of the nursing process in school-hospital, analyzed by a point of changing in the nursing departament organization. Assuming an innovating nature, the proposal demands an adaptative behavior of the nurse,the nursing and multiprofessional staffs, so that implementation of the assistence, in this perspective, can be effective and come to a high quality level. The work still points out, the stablishing of the training program and up-to-date nurses program in order to make them cut out for accomplishment of their roles as coordinator of nursing assistence.